2020
DOI: 10.1155/2020/4191806
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Ingress in Cement Mortars Exposed to Acidithiobacillus thiooxidans Bacteria

Abstract: Concrete structures placed in aggressive aqueous environments are vulnerable to degradation. Majority of studies have linked structural failures to the ingress of deleterious ions into the cement matrix. Some microbial activities may accelerate the penetration of harmful materials into the cement matrix and hence cause pronounced deterioration. This work reports a laboratory-simulated study carried out to determine the extent of chloride ingress in cement mortars exposed to Acidithiobacillus thiooxidans. Test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…It has also been reported that the formation of insoluble Mg(OH)2 (brucite) in the surface layer under the action of seawater does not inhibit Clpenetration [17], and the result of this experiment that the penetration of Clis not inhibited by the gypsum layer is a result similar to the past finding. Additionally, it is pointed out that the presence of microcracks in the concrete surface allows the penetration of chlorides into the concrete/steel interface and leads to corrosion of the rebar [18].…”
Section: Results Of Epma Mapping Analysismentioning
confidence: 99%
“…It has also been reported that the formation of insoluble Mg(OH)2 (brucite) in the surface layer under the action of seawater does not inhibit Clpenetration [17], and the result of this experiment that the penetration of Clis not inhibited by the gypsum layer is a result similar to the past finding. Additionally, it is pointed out that the presence of microcracks in the concrete surface allows the penetration of chlorides into the concrete/steel interface and leads to corrosion of the rebar [18].…”
Section: Results Of Epma Mapping Analysismentioning
confidence: 99%